Screening and Monitoring in Men Prescribed Testosterone Therapy in the U.S., 2001–2010. (March 2015) - Baillargeon, Jacques; Urban, Randall J.; Kuo, Yong-Fang; Holmes, Holly M.; Raji, Mukaila A.; Morgentaler, Abraham; Howrey, Bret T.; Lin, Yu-Li; Ottenbacher, Kenneth J.
Objectives: The Endocrine Society recommends testosterone therapy only in men with low serum testosterone levels, consistent symptoms of hypogonadism, and no signs of prostate cancer. We assessed screening and monitoring patterns in men receiving testosterone therapy in the U.S. Methods: We conducted a retrospective cohort study of 61, 474 men aged ⩾40 years, and with data available in one of the nation's largest commercial insurance databases, who received at least one prescription for testosterone therapy from 2001 to 2010. Results: In the 12 months before initiating treatment, 73.4% of male testosterone users received a serum testosterone test and 60.7% received a prostate-specific antigen (PSA) test. Among men who were tested, 19.5% did not meet Endocrine Society guidelines for low testosterone. In the 12 months after initiating treatment, 52.4% received a serum testosterone test and 43.3% received a PSA test. Multivariable analyses showed that those seen by either an endocrinologist or urologist were more likely to receive appropriate tests. Conclusions: A substantial number of men prescribed testosterone therapy did not receive testosterone or PSA testing before or after initiating treatment. In addition, almost one out of five treated men had baseline serum testosterone values above the threshold defined as normal by the Endocrine Society. Men treated by endocrinologists and urologists were more likely to have been treated according to guideline recommendations than men treated by other specialties, including primary care.